Anthocyanins, Anthocyanin-Rich Berries, and Cardiovascular Risks: Systematic Review and Meta-Analysis of 44 Randomized Controlled Trials and 15 Prospective Cohort Studies - Xu, Lin; Tian, Zezhong; Chen, Hong; Zhao, Yimin; Yang, Yan (Frontiers in Nutrition, 2021)
Objective: The associations between intake of anthocyanins and anthocyanin-rich berries and cardiovascular risks remained to be established. We aimed to quantitatively summarize the effects of purified anthocyanins and anthocyanin-rich berries on major surrogate markers of cardiovascular diseases (CVDs) and the longitudinal associations between dietary anthocyanins and CVD events. Methods: Meta-analysis of randomized controlled trials (RCTs) and prospective cohort studies. Results: We included 44 eligible RCTs and 15 prospective cohort studies in the present study. Pooled analysis of RCTs showed that purified anthocyanin supplementation could significantly reduce blood LDL cholesterol (weighted mean difference (WMD): -5.43 mg/dL, 95% CI: -8.96, -1.90 mg/dL; P = 0.003) and triglyceride (WMD: -6.18 mg/dL, 95% CI: -11.67, -0.69 mg/dL; P = 0.027) while increase HDL cholesterol (WMD: 11.49 mg/dL, 95% CI: 7.43, 15.55 mg/dL; P < 0.001) concentrations. Purified anthocyanins also markedly decreased circulating tumor necrosis factor alpha (WMD: -1.62 pg/mL, 95% CI: -2.76, -0.48 pg/mL; P = 0.005) and C-reactive protein (WMD: -0.028 mg/dL, 95% CI: -0.050, -0.005 mg/dL; P = 0.014). Besides, administration of anthocyanin-rich berries could significantly lower blood total cholesterol (WMD: -4.48 mg/dL, 95% CI: -8.94, -0.02 mg/dL; P = 0.049) and C-reactive protein (WMD: -0.046 mg/dL, 95% CI: -0.070, -0.022 mg/dL; P < 0.001). Neither purified anthocyanins nor anthocyanin-rich berries could cause any substantial improvements in BMI, blood pressure, or flow-mediated dilation. In addition, meta-analysis of prospective cohort studies suggested that high dietary anthocyanins were related to lower risk of coronary heart disease (relative risk (RR): 0.83, 95% CI: 0.72, 0.95; P = 0.009), total CVD incidence (RR: 0.73, 95% CI: 0.55, 0.97; P = 0.030), and total CVD deaths (RR: 0.91, 95% CI: 0.87, 0.96; P < 0.001). Conclusion: Habitual intake of anthocyanins and anthocyanin-rich berries could protect against CVDs possibly via improving blood lipid profiles and decreasing circulating proinflammatory cytokines.